2020
DOI: 10.35816/jiskh.v11i1.259
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Histopatologi dan Stadium Klinis Kanker Nasofaring

Abstract: Latar Belakang : Kanker Nasofaring merupakan penyakit endemik di beberapa bagian di Asia Tenggara dan Cina. Pada tahun 2018 terdapat 348.809 kasus baru dan 207.210 kematian yang disebabkan oleh kanker nasofaring. Insidensi kanker nasofaring akan meningkat setelah berusia 30 tahun dan insidensi tertinggi berada pada usia 45-55 tahun. Insidensi kanker nasofaring pada pria lebih tinggi 2-3 kali dibandingkan insidensi pada wanita. Pasien kanker nasofaing pada umumnya terdiagnosa pada stadium lanjut sehingga member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
2
3
0
1
Order By: Relevance
“…Based on data at the ENT Poly of Sanglah Hospital Denpasar in 2015 as many as 59.4% at the age of 46 to 65 years (4) . This data is in line with research at Dr. H. Abdul Moeloek Hospital, the highest nasopharyngeal carcinoma cases aged 46-55 years (5) . According to some studies, the incidence of nasopharyngeal carcinoma is mostly found in men.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on data at the ENT Poly of Sanglah Hospital Denpasar in 2015 as many as 59.4% at the age of 46 to 65 years (4) . This data is in line with research at Dr. H. Abdul Moeloek Hospital, the highest nasopharyngeal carcinoma cases aged 46-55 years (5) . According to some studies, the incidence of nasopharyngeal carcinoma is mostly found in men.…”
Section: Introductionsupporting
confidence: 91%
“…According to some studies, the incidence of nasopharyngeal carcinoma is mostly found in men. At Dr. Wahidin Sudirohusodo Hospital, nasopharyngeal carcinoma cases in men are 64.18% while women are 35.82% (5). Research by Dawolo (2017) states that the most nasopharyngeal carcinoma in men is 72.73%.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in our center reported that most patients with NPC mainly seek professional help due to neck lymph node metastases. The advanced stage contributes to the high mortality rate of NPC, stage III 15.4%, stage IVA 13.8%, and stage IVB 1.5% [3,14].…”
Section: Discussionmentioning
confidence: 99%
“…Bahwa pola pada penderita karsinoma pankreas berdasarkan umur, jenis kelamin, prosedur, ikterus, atau bukan ikterus dan predileksi . Karakteristik histopatologi dan stadium klinis kanker nasofaring, distribusi frekuensi kanker nasofaring berdasarkan jenis kelamin dan umur (Kuswandi et al, 2020). Diduga, terdapat tiga faktor yang berhubungan dengan KNF: virus Ebstein-Barr, genetik, dan faktor lingkungan.…”
Section: Hasil Dan Pembahasanunclassified